Konsep Cinta dalam Film Air Mata di Ujung Sajadah Menurut Perspektif Komunikasi Islam - Hayati, Riska; Anwar, Azrmiral; RM, Sulaiman; Tamrin Sikumbang, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to find out how the concept of love in the movie Air Mata di Ujung Sajadah according to the Islamic Communication Perspective. The problem described is the concept of love of biological mothers and adoptive parents to their children and how communication is established between the two parties in maintaining child custody. As it is known that the phenomenon that occurs in this film is that the biological mother does not know that her child is still alive, namely being cared for and raised by others for seven years, the problem arises when she finds out that her child actually did not die, but after giving birth her child was given by her own mother to someone else. This research is a type of content analysis research using a qualitative approach, which prioritizes the presentation of structured data, and provides a detailed description of the object of research in the form of communication messages. Qualitative content analysis is defined as a scientific research technique aimed at knowing the characteristic description of the message content and drawing inferences contained in the message content. The results showed that the concept of love in the movie Air Mata di Ujung Sajadah is packaged so well. Mother's love is an unconditional statement towards the child's life and needs. Absolute care and responsibility are also given by parents for the sustainability of the child's life and growth. Parents also instill love for life.